A closer look on the coordination of soft nitrogen-donor ligands to Cm(iii): SO3-Ph-BTBP. Issue 31 (21st July 2016) - Trumm, M.; Wagner, C.; Schimmelpfennig, B.; Geist, A.; Panak, P. J.
Abstract : The combination of theory, VSBS and TRLFS revealed new insights into the coordination structure of [Cm(SO3 -Ph-BTBP)2 ] 5− . Abstract : We present a combined theoretical and experimental study on the recently developed hydrophilic SO3 -Ph-BTBP ligand. Vibronic side band spectroscopy and time-resolved laser fluorescence spectroscopy (TRLFS) were employed to prove the theoretical prediction of the ligand's coordination mode.